Geo-Strategic Competition in Aesthetic Surgery: Push–Pull Dynamics Driving Indonesian Patients Abroad - Wati, Dian Ika; Wening, Nur (Technium Social Sciences Journal, 2025)
The increasing flow of Indonesian patients seeking aesthetic surgery abroad reflects a complex interplay of geo-strategic competition among regional and global medical hubs. This study examines the push-pull dynamics influencing outbound cosmetic surgery tourism from Indonesia, focusing on destination competitiveness, patient decision-making pathways, and cross-border marketing strategies. A scoping review of peer-reviewed literature (Scopus Q1–Q3) and policy documents is combined with stakeholder interviews to explore how perceived quality, service experience, pricing transparency, and cultural affinity drive patient preferences. The findings reveal that Malaysia and Singapore leverage cultural proximity and integrated service packages, while South Korea capitalizes on global K-beauty branding and surgical specialization. The competitive landscape is further shaped by accreditation standards, digital marketing, and government facilitation policies. Policy recommendations are proposed to strengthen domestic service quality, enhance patient trust, and position Indonesia as a competitive node in the regional aesthetic surgery market.